Kekuatan dan Ketidakadilan dalam Kehidupan Perempuan pada Novel "Beloved" Karya Toni Morrison - Raidinoor, Muhammad (Serat: Journal of Literary & Cultural Studies, 2024)
The novel "Beloved" by Toni Morrison reveals a bitter narrative of women's lives, especially through its central character, Sethe. This research aims to explore the depth of power and injustice experienced by women in a post-fear context. Using a feminist analytical approach, this research demonstrates how Sethe, as an African American woman, confronts systemic forces and a history of abuse that result in injustice in her life. Sethe's depiction as a modern heroine reveals the power of women to persevere and create meaning in difficult situations. However, his existence is also a tragic story of injustice, especially in the context of his loss of human rights and traumatic experiences. The novel highlights how Sethe and other women struggle against racial, social, and gender injustice, creating a narrative full of resistance to power structures that threaten their well-being. Analysis of language, characters, and historical context helps bring to light the complex dynamics of power and injustice in women's lives. Through this exploration, this research seeks to provide in-depth insight into the role of women in navigating a harsh world and highlight the importance of hearing their voices in historical narratives.